Physiological Responses of Tomato and Cucumber Seedlings under Different Light–Dark Cycles - Pedro García-Caparrós; Francisco Sabio; Francisco Javier Barbero; Rosa María Chica; María Teresa Lao (Agronomy, 2020)
Tomato and cucumber seedlings were grown in a growth chamber to evaluate the effects of different cycles of light–dark exposure conditions (T0 (control treatment) (1 cycle of 24 h distributed in 18 h of light exposure and six hours of dark), T1 (two cycles of 12 h distributed in nine hours of light exposure and three hours of dark) and T2 (three cycles of eight hours distributed in six hours of light exposure and two hours of dark) on growth, nutrient status, pigment concentration and physiological changes. Total dry weight showed different behaviors in both species, since in tomato the total dry weight remained unchanged under varying light–dark cycles, whereas in cucumber seedlings there was a clear decrease compared to the control treatment. In both species, plants grown under T2 showed the best water content. Nitrogen, P and K content—as well as partitioning in the different organs of the plants—displayed different patterns under varying cycles of light–dark conditions in both species. Chlorophyll (b and a + b) concentration decreased significantly in both species in T1 and T2 compared to the control treatment (T0). At physiological level, the concentration of total soluble sugars and proline in leaf showed the highest value in the control treatment with 18 h of light and six hours of dark.